Motivating creativity: a critical review of past literature - Altabaa, Homam; Azahari, Siti Hasanah (International Institute for Muslim Unity, IIUM, 2021)
Research on creativity has been gaining more interest from scholars in various fields. Creativity used to be perceived as subject that was mainly relevant to professionals in the fields of arts and music. However, today creativity is acknowledged as a scientific subject that is relevant to engineering, architecture as well as human sciences. Thus, its meanings are varied and may differ from one scholar to another. Nevertheless, a majority of researchers agree that creativity may be defined as a product that is novel, original, and unique. Studies on the subject have existed for decades, from the days many thought of creativity as an innate and divine ability originating from God, and to recent years where scholars have deemed creativity as a learnable trait. Yet, not everyone is motivated to be creative. As modern problems are becoming increasingly complicated, everyone in the society including parents, employers, and teachers must play their part to encourage creativity. Furthermore, past research has examined the various forms of motivation that encourage creativity. Hence, this article briefly discusses the history and definition of and reviews past literature on motivation in creativity in hopes that it can help enhance creativity among children, students, employees, etc.